Bioerosion by the sea urchin Diadema mexicanum along Eastern Tropical Pacific coral reefs - Alvarado Barrientos, Juan José (2016)
Bioerosion is a natural process in coral reefs. It is fundamental to the health of these ecosystems. In the Eastern Tropical Pacific (ETP) coral reefs, the most important bioeroders are sponges, bivalves, sea urchins and the fish Arothron meleagris. In the 1980s, El Niño caused high coral mortality and an increase in macroalgal growth. As a result, greater sea urchin bioerosion occurred. This weakened the reef framework. Considering the high vulnerability of the ETP coral reefs, the goal of this study was to determine the current bioerosion impact of the sea urchin Diadema mexicanum along the western coasts of Mexico, El Salvador, Costa Rica and Panamá. The balance between coral bioaccretion and sea urchin bioerosion was also calculated. Between 2009 and 2010, in 12 coral reefs localities, D. mexicanum density, bottom cover and rugosity were quantified along band transects. The daily bioerosion rate was obtained from the amount of carbonates evacuated by sea urchins per unit time. The rate of coral accretion was calculated by multiplying the coral growth rate of the dominant genus by the density of their skeleton and by their specific coral cover. The localities were dissimilar (R = 0.765, P < 0.001) in terms of live coral cover, crustose calcareous algae, turf cover, rugosity index, and density and size of D. mexicanum. At all sites, with the exception of Bahía Culebra (Costa Rica), coral bioerosion was less than coral bioaccretion. Diadema mexicanum plays a dominant role in the balance of carbonates in the ETP, but this depends on reef condition (protection, overfishing, eutrophication) and so the impacts can be either positive or negative.